A surface wear-resistant coating for a bicycle synchronous belt and a method for preparing the same
Patent Information
- Application Number
- CN202610914624.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2046-06-24
AI Technical Summary
另一方面,自行车大多在户外骑行,日常停放也不是露天环境,同步带长期受到太阳光的辐射,紫外线能量会破坏聚合物分子结构,加速材料老化,影响使用寿命,增加安全风险
第一,将柠檬酸、2-氨基乙硫醇盐酸盐反应得到吡啶酮类紫外吸收单体;将炭黑与KH550反应,在炭黑表面引入氨基;再与吡啶酮类紫外吸收单体上的羧基反应,得到改性炭黑;该操作在炭黑上负载了大量的吡啶酮类紫外吸收剂,可以大幅度提升涂层的耐候性能,将小分子的紫外吸收剂以化学键的形式负载到炭黑上,能预防紫外吸收剂的析出和流失,达到长效的耐候作用。
Smart Images

Figure SMS_2 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating processing technology, specifically to a wear-resistant coating for the surface of a bicycle timing belt and its preparation method. Background Technology
[0002] Bicycle timing belts are annular toothed transmission belts used in bicycle drivetrains. They are a core component of chainless bicycle drivetrains, relying on the meshing of teeth and pulleys to transmit power, replacing traditional chains to achieve a quiet, maintenance-free riding experience. They offer advantages such as requiring no lubricant, being resistant to dust and rust, low noise, and lightweight. However, timing belts inevitably experience wear during use, and improving their wear resistance has always been a research topic in industrial applications. Furthermore, bicycles are mostly ridden outdoors, and daily parking is not in an open-air environment. Timing belts are exposed to sunlight for extended periods, and ultraviolet radiation can damage the polymer molecular structure, accelerating material aging, affecting service life, and increasing safety risks. Adding anti-aging agents directly to the raw materials is an effective method, but most anti-aging agents are small molecules that are easily leached and lost, making it difficult to achieve long-term protective effects. Summary of the Invention
[0003] In view of the above-mentioned problems of the prior art, the present invention aims to provide a wear-resistant coating for the surface of bicycle timing belts and a method for preparing the same. The wear-resistant coating for the surface of bicycle timing belts prepared by this method has excellent wear resistance, weather resistance and high adhesion strength, so as to effectively solve or at least alleviate one or more problems existing in the prior art.
[0004] This invention provides the following technical solution: A method for preparing a wear-resistant coating on the surface of a bicycle timing belt includes the following steps: (1) Citric acid and 2-aminoethanethiol hydrochloride were reacted to obtain pyridinone-based ultraviolet-absorbing monomers; (2) Pretreated carbon black was prepared by reacting carbon black with KH550; modified carbon black was obtained by reacting the pretreated carbon black with pyridone-type ultraviolet absorption monomers. (3) Pre-modified polytetrafluoroethylene (PTFE) micro powder was prepared by reacting it with maleic anhydride after pre-irradiation; modified PTFE micro powder was prepared by reacting the pre-modified PTFE micro powder with dopamine. (4) HNBR rubber, modified polytetrafluoroethylene micro powder, modified carbon black, trimethylolpropane trimethacrylate, stearic acid, accelerator and vulcanizing agent are mixed to obtain a mixture; the mixture is scraped onto the fabric base belt and vulcanized to obtain a wear-resistant coating on the surface of the bicycle timing belt.
[0005] Furthermore, the preparation method of the pyridone-based ultraviolet-absorbing monomer in step (1) is as follows: Citric acid and 2-aminoethanethiol hydrochloride were dissolved in 2-3 times the mass of citric acid in deionized water at a molar ratio of 1:1. The mixture was dehydrated at 130-135℃ for 10-12 hours. After cooling to room temperature, 5-6 times the mass of citric acid in deionized water was added and mixed thoroughly. The mixture was then filtered, washed with water, and dried under vacuum at 80-85℃ for 20-24 hours to obtain a pyridinone-based ultraviolet-absorbing monomer.
[0006] Furthermore, the reaction principle of the pyridone-based ultraviolet-absorbing monomer is as follows: .
[0007] Furthermore, the method for preparing the pretreated carbon black in step (2) is as follows: Weigh carbon black and KH550 at a mass ratio of 1:0.15~0.2; mix KH550, anhydrous ethanol, and deionized water at a mass ratio of 1:4~5:0.4~0.6, and sonicate for 10~20 min to obtain a treatment solution; mix carbon black, anhydrous ethanol, and deionized water at a mass ratio of 1:35~40:8~10, add to the treatment solution, stir at 50~60℃ for 4~5 h, filter, wash with water, and vacuum dry at 75~80℃ for 10~12 h to obtain pretreated carbon black; The KH550 is γ-aminopropyltriethoxysilane; The carbon black is carbon black N330.
[0008] Furthermore, the method for preparing the modified carbon black in step (2) is as follows: Pretreated carbon black, pyridone-based UV-absorbing monomers, and dichloromethane were mixed in a mass ratio of 1:0.5~0.6:16~20. An equimolar amount of DCC and 0.04~0.06 times the molar amount of DMAP were added. The mixture was stirred at room temperature for 7~8 hours, filtered, washed with water, and dried under vacuum at 75~80℃ for 14~16 hours to obtain modified carbon black. The DCC is dicyclohexylcarbodiimide; The DMAP is 4-dimethylaminopyridine.
[0009] Furthermore, the preparation method of the pre-modified polytetrafluoroethylene micro powder in step (3) is as follows: The polytetrafluoroethylene micropowder was placed in an air atmosphere at room temperature. 60Pretreated polytetrafluoroethylene (PTFE) micropowder was obtained by irradiating a Co radioactive source with a gamma dose of 100 kGy. The pretreated PTFE micropowder, maleic anhydride, and acetone glycerol were mixed in a mass ratio of 1:0.1~0.12:5~6. A polymerization inhibitor of 0.04~0.06 times the mass of maleic anhydride and a sensitizer of 0.1~0.12 times the mass of maleic anhydride were added. The mixture was purged with nitrogen and reacted in a water bath at 70~75℃ for 4~5 h. The mixture was then extracted with acetone for 48 h and vacuum dried at 50~60℃ for 6~8 h to obtain pre-modified PTFE micropowder. The 60 The Co radioactive source has an activity of 1.85 × 10⁻⁶. 14 Bq; The polytetrafluoroethylene micro powder is PTFE-0143; The polymerization inhibitor is ferrous ammonium sulfate; The sensitizer is concentrated sulfuric acid with a concentration of 98%.
[0010] Furthermore, the preparation method of the modified polytetrafluoroethylene micro powder in step (3) is as follows: Premodified polytetrafluoroethylene (PTFE) micropowder and N,N-dimethylformamide were mixed at a mass ratio of 1:10~12, and sonicated for 10~20 min. Dopamine was added at 0.3~0.4 times the mass of the premodified PTFE micropowder, and the mixture was reacted at 135~145℃ for 3~4 h. After cooling to room temperature, the mixture was filtered, washed with water, and vacuum dried at 50~60℃ for 10~15 h to obtain modified PTFE micropowder.
[0011] Furthermore, the preparation method of the mixture in step (4) is as follows: By weight, 100 parts of HNBR rubber and 50-60 parts of modified polytetrafluoroethylene micro powder are placed in an internal mixer and mixed at 125-135℃ and 40-50 r / min for 5-6 minutes. Then, 20-24 parts of modified carbon black, 12-14 parts of trimethylolpropane trimethacrylate, 0.8-1 parts of stearic acid, and 0.5-0.7 parts of accelerator are added and the mixture is continued to be mixed for 3-5 minutes. The temperature is then lowered to 85-95℃, and 0.8-1 parts of vulcanizing agent are added. The mixture is continued to be mixed for 8-10 minutes to obtain the mixture. The HNBR rubber is HNBR 3305L; The accelerator is dibenzothiazole disulfide; The vulcanizing agent is vulcanizing agent S-80.
[0012] Furthermore, the fabric base tape in step (4) is one of nylon, aramid, or polyester.
[0013] The present invention also provides a wear-resistant coating for bicycle timing belts prepared by the above-described method for preparing a wear-resistant coating for bicycle timing belts.
[0014] The present invention has the following technical advantages and beneficial effects: First, citric acid and 2-aminoethanethiol hydrochloride are reacted to obtain pyridone-based UV-absorbing monomers. Carbon black is then reacted with KH550 to introduce amino groups onto the carbon black surface. These amino groups are then reacted with the carboxyl groups on the pyridone-based UV-absorbing monomers to obtain modified carbon black. This process loads a large amount of pyridone-based UV absorbers onto the carbon black, which can significantly improve the weather resistance of the coating. Loading small-molecule UV absorbers onto the carbon black in the form of chemical bonds can prevent the precipitation and loss of UV absorbers, achieving long-lasting weather resistance.
[0015] Secondly, the addition of carbon black can act as a reinforcing filler to improve the wear resistance of the coating. However, carbon black is an inorganic material with poor compatibility with rubber, and direct addition can easily lead to uneven dispersion. The surface treatment with silane coupling agent KH550 improves the dispersion of carbon black in the coating, thereby fully exerting the wear resistance effect.
[0016] Third, polytetrafluoroethylene (PTFE) has the characteristics of low friction coefficient and good self-lubrication. However, due to its low surface energy and high crystallinity, PTFE is difficult to diffuse and entangle molecular chains, resulting in poor adhesion between PTFE and other materials. This application introduces a large number of mussel-like catechol structures into PTFE by radiation grafting, which then reacts with the amino groups on dopamine. This improves the compatibility between PTFE micropowder and rubber, making the mixture tightly bonded. At the same time, the mussel-like catechol structures introduced into the PTFE micropowder have strong adhesion and can adhere to the surface of the fabric substrate through hydrogen bonding, oxidative crosslinking, etc., further improving the wear resistance and adhesion of the coating. Detailed Implementation
[0017] To enable those skilled in the art to further understand the present invention, specific embodiments of the present invention are described in detail below. However, it should be understood that the embodiments of the present invention described herein are merely exemplary, and the present invention is not limited to these embodiments.
[0018] Example 1 This embodiment provides a method for preparing a wear-resistant coating on the surface of a bicycle timing belt, including the following preparation steps: (1) Citric acid and 2-aminoethanethiol hydrochloride were dissolved in deionized water at a molar ratio of 1:1, and the mixture was dehydrated at 130°C for 12 h. After cooling to room temperature, deionized water at 5 times the mass of citric acid was added and mixed evenly. The mixture was filtered, washed with water, and dried under vacuum at 80°C for 24 h to obtain pyridinone-type ultraviolet absorber monomers. (2) Weigh carbon black and KH550 at a mass ratio of 1:0.15; mix KH550, anhydrous ethanol and deionized water at a mass ratio of 1:4:0.4 and sonicate for 10 min to obtain a treatment solution; mix carbon black, anhydrous ethanol and deionized water at a mass ratio of 1:35:8, add the treatment solution, stir at 50℃ for 5 h, filter, wash with water, and vacuum dry at 75℃ for 12 h to obtain pretreated carbon black; mix pretreated carbon black, pyridone UV-absorbing monomer and dichloromethane at a mass ratio of 1:0.5:16, add an equimolar amount of DCC and 0.04 times the molar amount of DMAP of pyridone UV-absorbing monomer, stir at room temperature for 7 h, filter, wash with water, and vacuum dry at 75℃ for 16 h to obtain modified carbon black; (3) Place the polytetrafluoroethylene micro powder in an air atmosphere at room temperature. 60 Pretreated polytetrafluoroethylene (PTFE) micropowder was obtained by irradiating a Co radioactive source with an absorbed dose of 100 kGy. The pretreated PTFE micropowder, maleic anhydride, and acetone glycerol were mixed at a mass ratio of 1:0.1:5. Ferrous ammonium sulfate (0.04 times the mass of maleic anhydride) and concentrated sulfuric acid (0.1 times the mass of maleic anhydride) were added. The mixture was purged with nitrogen and reacted in a water bath at 70°C for 5 hours. Acetone extraction was performed for 48 hours, followed by vacuum drying at 50°C for 8 hours to obtain pre-modified PTFE micropowder. Pre-modified PTFE micropowder and N,N-dimethylformamide were mixed at a mass ratio of 1:10 and sonicated for 10 minutes. Dopamine (0.3 times the mass of the pre-modified PTFE micropowder) was added, and the mixture was reacted at 135°C for 4 hours. After cooling to room temperature, the mixture was filtered, washed with water, and vacuum dried at 50°C for 15 hours to obtain modified PTFE micropowder. (4) By weight, 100 parts of HNBR rubber and 50 parts of modified polytetrafluoroethylene micro powder were placed in a mixer and mixed at 125°C and 40 r / min for 6 min. 20 parts of modified carbon black, 12 parts of trimethylolpropane trimethacrylate, 0.8 parts of stearic acid, and 0.5 parts of dibenzothiazole disulfide were added and mixed for another 5 min. The mixture was cooled to 85°C and 0.8 parts of vulcanizing agent S-80 were added. The mixture was then mixed for another 10 min to obtain a mixture. The mixture was then coated onto nylon at a coating temperature of 80°C, a thickness of 0.3 mm, and a speed of 40 cm / min. After cooling to room temperature, the mixture was placed in a vulcanizing machine and vulcanized at 4 MPa and 160°C for 20 min to obtain a wear-resistant coating on the surface of the bicycle timing belt.
[0019] Example 2 A method for preparing a wear-resistant coating on the surface of a bicycle timing belt, the method comprising the following steps: (1) Citric acid and 2-aminoethanethiol hydrochloride were dissolved in deionized water at a molar ratio of 1:1, and the mixture was dehydrated at 133°C for 11 h. After cooling to room temperature, deionized water at 5 times the mass of citric acid was added and mixed evenly. The mixture was filtered, washed with water, and dried under vacuum at 82°C for 22 h to obtain pyridinone-type ultraviolet absorber monomers. (2) Weigh carbon black and KH550 in a mass ratio of 1:0.18; mix KH550, anhydrous ethanol and deionized water in a mass ratio of 1:4:0.5 and sonicate for 15 min to obtain a treatment solution; mix carbon black, anhydrous ethanol and deionized water in a mass ratio of 1:38:9, add the treatment solution, stir at 55℃ for 4.5 h, filter, wash with water, and vacuum dry at 77℃ for 11 h to obtain pretreated carbon black; mix pretreated carbon black, pyridone UV-absorbing monomer and dichloromethane in a mass ratio of 1:0.55:18, add an equimolar amount of DCC and 0.05 times the molar amount of DMAP of pyridone UV-absorbing monomer, stir at room temperature for 7.5 h, filter, wash with water, and vacuum dry at 77℃ for 15 h to obtain modified carbon black; (3) Place the polytetrafluoroethylene micro powder in an air atmosphere at room temperature. 60 Pretreated polytetrafluoroethylene (PTFE) micropowder was obtained by irradiating a Co radioactive source with an absorbed dose of 100 kGy. The pretreated PTFE micropowder, maleic anhydride, and acetone glycerol were mixed at a mass ratio of 1:0.11:5.5. Ferrous ammonium sulfate (0.05 times the mass of maleic anhydride) and concentrated sulfuric acid (0.11 times the mass of maleic anhydride) were added. The mixture was purged with nitrogen and reacted in a water bath at 72°C for 4.5 h. Acetone extraction was performed for 48 h, followed by vacuum drying at 55°C for 7 h to obtain pre-modified PTFE micropowder. Pre-modified PTFE micropowder and N,N-dimethylformamide were mixed at a mass ratio of 1:11 and sonicated for 15 min. Dopamine (0.35 times the mass of pre-modified PTFE micropowder) was added, and the mixture was reacted at 140°C for 3.5 h. After cooling to room temperature, the mixture was filtered, washed with water, and vacuum dried at 55°C for 13 h to obtain modified PTFE micropowder. (4) By weight, 100 parts of HNBR rubber and 55 parts of modified polytetrafluoroethylene micro powder were placed in a mixer and mixed at 130°C and 45 r / min for 5.5 min. 22 parts of modified carbon black, 13 parts of trimethylolpropane trimethacrylate, 0.9 parts of stearic acid, and 0.6 parts of dibenzothiazole disulfide were added and mixed for another 4 min. The mixture was cooled to 90°C and 0.9 parts of vulcanizing agent S-80 were added and mixed for another 9 min to obtain a mixture. The mixture was then coated onto nylon at a coating temperature of 80°C, a thickness of 0.3 mm, and a speed of 40 cm / min. After cooling to room temperature, the mixture was placed in a vulcanizing machine and vulcanized at 4 MPa and 160°C for 20 min to obtain a wear-resistant coating on the surface of the bicycle timing belt.
[0020] Example 3 A method for preparing a wear-resistant coating on the surface of a bicycle timing belt, the method comprising the following steps: (1) Citric acid and 2-aminoethanethiol hydrochloride were dissolved in deionized water at a molar ratio of 1:1, and the mixture was dehydrated at 135°C for 10 h. After cooling to room temperature, deionized water at 6 times the mass of citric acid was added and mixed evenly. The mixture was filtered, washed with water, and dried under vacuum at 85°C for 20 h to obtain pyridinone-type ultraviolet absorber monomers. (2) Weigh carbon black and KH550 in a mass ratio of 1:0.2; mix KH550, anhydrous ethanol and deionized water in a mass ratio of 1:5:0.6 and sonicate for 20 min to obtain a treatment solution; mix carbon black, anhydrous ethanol and deionized water in a mass ratio of 1:40:10, add the treatment solution, stir at 60℃ for 4 h, filter, wash with water, and vacuum dry at 80℃ for 10 h to obtain pretreated carbon black; mix pretreated carbon black, pyridone UV-absorbing monomer and dichloromethane in a mass ratio of 1:0.6:20, add an equimolar amount of DCC and 0.06 times the molar amount of DMAP of pyridone UV-absorbing monomer, stir at room temperature for 8 h, filter, wash with water, and vacuum dry at 80℃ for 14 h to obtain modified carbon black; (3) Place the polytetrafluoroethylene micro powder in an air atmosphere at room temperature. 60 Pretreated polytetrafluoroethylene (PTFE) micropowder was obtained by irradiating a Co radioactive source with an absorbed dose of 100 kGy. The pretreated PTFE micropowder, maleic anhydride, and acetone glycerol were mixed at a mass ratio of 1:0.12:6. Ferrous ammonium sulfate (0.06 times the mass of maleic anhydride) and concentrated sulfuric acid (0.12 times the mass of maleic anhydride) were added. The mixture was purged with nitrogen and reacted in a water bath at 75°C for 4 hours. Acetone extraction was performed for 48 hours, followed by vacuum drying at 60°C for 6 hours to obtain pre-modified PTFE micropowder. Pre-modified PTFE micropowder and N,N-dimethylformamide were mixed at a mass ratio of 1:12 and sonicated for 20 minutes. Dopamine (0.4 times the mass of the pre-modified PTFE micropowder) was added, and the mixture was reacted at 145°C for 3 hours. After cooling to room temperature, the mixture was filtered, washed with water, and vacuum dried at 60°C for 10 hours to obtain modified PTFE micropowder. (4) By weight, 100 parts of HNBR rubber and 60 parts of modified polytetrafluoroethylene powder were placed in a mixer and mixed at 135°C and 50 r / min for 5 min. 24 parts of modified carbon black, 14 parts of trimethylolpropane trimethacrylate, 1 part of stearic acid, and 0.7 parts of dibenzothiazole disulfide were added and mixed for another 3 min. The mixture was cooled to 95°C and 1 part of vulcanizing agent S-80 was added. The mixture was then mixed for another 8 min to obtain a mixture. The mixture was then coated onto nylon at a coating temperature of 80°C, a thickness of 0.3 mm, and a speed of 40 cm / min. After cooling to room temperature, the mixture was placed in a vulcanizing machine and vulcanized at 4 MPa and 160°C for 20 min to obtain a wear-resistant coating on the surface of the bicycle timing belt.
[0021] The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (2) is modified as follows: carbon black and KH550 are weighed at a mass ratio of 1:0.18; KH550, anhydrous ethanol, and deionized water are mixed at a mass ratio of 1:4:0.5 and sonicated for 15 min to obtain a treatment solution; carbon black, anhydrous ethanol, and deionized water are mixed at a mass ratio of 1:38:9, added to the treatment solution, stirred at 55°C for 4.5 h, filtered, washed with water, and vacuum dried at 77°C for 11 h to obtain pretreated carbon black. In step (4), "modified carbon black" is replaced with "pretreated carbon black".
[0022] The difference between Comparative Example 2 and Example 2 is that steps (1) and (2) are omitted, and "modified carbon black" in step (4) is replaced with "carbon black".
[0023] The difference between Comparative Example 3 and Example 2 is that step (3) is omitted, and "modified polytetrafluoroethylene micro powder" in step (4) is replaced with "polytetrafluoroethylene micro powder".
[0024] Test example: Preparation of standard specimens: The mixtures obtained from the examples and comparative examples were placed in a vulcanizing machine and vulcanized at 4 MPa and 160°C for 20 min. Standard specimens were prepared according to relevant test standards and then tested.
[0025] Abrasion resistance: The abrasion resistance of the examples and comparative examples was tested using a DIN abrasion tester according to the national standard GB / T9867-2008.
[0026] Adhesion: The adhesion was tested using a peel force tester in accordance with the national standard GB / T2792-2014.
[0027] Weather resistance: The tensile strength of the test examples and comparative examples was determined according to GB / T 528—2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", denoted as P; the total length of the specimen was 75 mm, the thickness was 2 mm, the working width was 4 mm, and the tensile rate was 500 mm·min.-1 The examples and comparative examples were subjected to aging tests in an ultraviolet aging chamber with an irradiation intensity of 8×60W, a distance of 20cm between the sample and the light source, and a duration of 15 days. After the aging test, the tensile strength Q was tested, and the strength retention rate was calculated as Q / P×100%.
[0028] The experimental data from the above experiments are recorded in Table 1.
[0029] Table 1
[0030] Conclusions: In Table 1, the wear volume of Examples 1-3 is significantly smaller than that of Comparative Example 2, indicating that surface treatment of carbonization with KH550 can improve the dispersibility of carbon black in the coating, prevent agglomeration, fully utilize the reinforcing effect of carbon black, and improve the wear resistance of the coating. The wear amount of Examples 1-3 is significantly smaller than that of Comparative Example 3, and the peel strength of Examples 1-3 is significantly greater than that of Comparative Example 3, indicating that modification of polytetrafluoroethylene (PTFE) micropowder can improve the compatibility between PTFE micropowder and rubber, making the mixture tightly bonded. At the same time, the introduction of mussel-like catechol structure into PTFE micropowder has strong adhesion and can adhere to the surface of the fabric substrate through hydrogen bonding, oxidative crosslinking, etc., further improving the wear resistance and adhesion of the coating.
[0031] In Table 1, the strength retention rates of Examples 1-3 are significantly higher than those of Comparative Examples 1-2, indicating that the reaction of citric acid and 2-aminoethanethiol hydrochloride yields pyridone-based UV-absorbing monomers; the reaction of carbon black with KH550 and pyridone-based UV-absorbing monomers yields modified carbon black; and the loading of pyridone-based UV absorbers onto carbon black significantly improves the weather resistance of the coating.
[0032] The terms "comprising" and "including" as used in this invention include both cases where the invention consists only of the included elements and cases where it includes other elements in addition to the included elements.
[0033] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the present invention. The scope of the present invention is broadly defined within the scope of the technical solutions of this application. Any technical entity or method implemented by others that is completely identical to or an equivalent modification of the technical solutions defined in the scope of the present application shall be considered to be covered within the scope of the technical solutions of this application.
Claims
1. A method for preparing a wear-resistant coating on the surface of a bicycle timing belt, characterized in that, Includes the following steps: (1) Citric acid and 2-aminoethanethiol hydrochloride were reacted to obtain pyridinone-based ultraviolet-absorbing monomers; (2) Pretreated carbon black was prepared by reacting carbon black with KH550; modified carbon black was obtained by reacting the pretreated carbon black with pyridone-type ultraviolet absorption monomers. (3) Pre-modified polytetrafluoroethylene (PTFE) micro powder was prepared by reacting it with maleic anhydride after pre-irradiation; modified PTFE micro powder was prepared by reacting the pre-modified PTFE micro powder with dopamine. (4) HNBR rubber, modified polytetrafluoroethylene micro powder, modified carbon black, trimethylolpropane trimethacrylate, stearic acid, accelerator and vulcanizing agent are mixed to obtain a mixture; the mixture is scraped onto the fabric base belt and vulcanized to obtain a wear-resistant coating on the surface of the bicycle timing belt. The preparation method of the mixture is as follows: By weight, 100 parts of HNBR rubber and 50-60 parts of modified polytetrafluoroethylene micro powder are placed in an internal mixer and mixed at 125-135℃ and 40-50 r / min for 5-6 minutes. Then, 20-24 parts of modified carbon black, 12-14 parts of trimethylolpropane trimethacrylate, 0.8-1 parts of stearic acid, and 0.5-0.7 parts of accelerator are added and the mixture is continued to be mixed for 3-5 minutes. The temperature is then lowered to 85-95℃, and 0.8-1 parts of vulcanizing agent are added. The mixture is continued to be mixed for 8-10 minutes to obtain the mixture.
2. The method for preparing the wear-resistant coating on the surface of a bicycle timing belt according to claim 1, characterized in that, The preparation method of the pyridone-based ultraviolet-absorbing monomer in step (1) is as follows: Citric acid and 2-aminoethanethiol hydrochloride were dissolved in 2-3 times the mass of citric acid in deionized water at a molar ratio of 1:
1. The mixture was dehydrated at 130-135℃ for 10-12 hours. After cooling to room temperature, 5-6 times the mass of citric acid in deionized water was added and mixed thoroughly. The mixture was then filtered, washed with water, and dried to obtain pyridinone-based ultraviolet-absorbing monomers.
3. The method for preparing the wear-resistant coating on the surface of a bicycle timing belt according to claim 2, characterized in that, The reaction principle of the pyridone-based ultraviolet-absorbing monomers is as follows: 。 4. The method for preparing the wear-resistant coating on the surface of a bicycle timing belt according to claim 1, characterized in that, The method for preparing the pretreated carbon black in step (2) is as follows: Weigh carbon black and KH550 at a mass ratio of 1:0.15~0.2; mix KH550, anhydrous ethanol, and deionized water at a mass ratio of 1:4~5:0.4~0.6, and sonicate for 10~20 min to obtain a treatment solution; mix carbon black, anhydrous ethanol, and deionized water at a mass ratio of 1:35~40:8~10, add to the treatment solution, stir at 50~60℃ for 4~5 h, filter, wash with water, and dry to obtain pretreated carbon black; The KH550 is γ-aminopropyltriethoxysilane; The carbon black is carbon black N330.
5. The method for preparing the wear-resistant coating on the surface of a bicycle timing belt according to claim 1, characterized in that, The method for preparing the modified carbon black in step (2) is as follows: Pretreated carbon black, pyridone-based UV-absorbing monomers, and dichloromethane were mixed in a mass ratio of 1:0.5~0.6:16~20. An equimolar amount of DCC and 0.04~0.06 times the molar amount of DMAP were added. The mixture was stirred at room temperature for 7~8 hours, filtered, washed with water, and dried to obtain modified carbon black. The DCC is dicyclohexylcarbodiimide; The DMAP is 4-dimethylaminopyridine.
6. The method for preparing the wear-resistant coating on the surface of a bicycle timing belt according to claim 1, characterized in that, The preparation method of the pre-modified polytetrafluoroethylene micro powder in step (3) is as follows: The polytetrafluoroethylene micropowder was placed in an air atmosphere at room temperature. 60 Pretreated polytetrafluoroethylene (PTFE) micropowder was obtained by γ-irradiation with a Co radioactive source. The pretreated PTFE micropowder, maleic anhydride, and acetone glycerol were mixed in a mass ratio of 1:0.1~0.12:5~6. A polymerization inhibitor of 0.04~0.06 times the mass of maleic anhydride and a sensitizer of 0.1~0.12 times the mass of maleic anhydride were added. The mixture was purged with nitrogen and reacted in a water bath at 70~75℃ for 4~5 hours. The mixture was then extracted with acetone for 48 hours and vacuum dried at 50~60℃ for 6~8 hours to obtain pre-modified PTFE micropowder. The 60 The Co radioactive source has an activity of 1.85 × 10⁻⁶. 14 Bq; The polytetrafluoroethylene micro powder is PTFE-0143; The polymerization inhibitor is ferrous ammonium sulfate; The sensitizer is concentrated sulfuric acid.
7. The method for preparing the wear-resistant coating on the surface of a bicycle timing belt according to claim 1, characterized in that, The preparation method of the modified polytetrafluoroethylene micro powder in step (3) is as follows: Premodified polytetrafluoroethylene (PTFE) micropowder and N,N-dimethylformamide were mixed at a mass ratio of 1:10~12, and sonicated for 10~20 min. Dopamine was added at 0.3~0.4 times the mass of the premodified PTFE micropowder, and the mixture was reacted at 135~145℃ for 3~4 h. After cooling to room temperature, the mixture was filtered, washed with water, and dried to obtain modified PTFE micropowder.
8. The method for preparing the wear-resistant coating on the surface of a bicycle timing belt according to claim 1, characterized in that, The HNBR rubber mentioned in step (4) is HNBR 3305L; The accelerator is dibenzothiazole disulfide; The vulcanizing agent is vulcanizing agent S-80.
9. The method for preparing the wear-resistant coating on the surface of a bicycle timing belt according to claim 1, characterized in that, The fabric base tape in step (4) is one of nylon, aramid, or polyester.
10. A wear-resistant coating for a bicycle timing belt surface prepared by the method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Anti-ultraviolet carbon black color paste as well as preparation method and application thereof
CN121802691A
Rubber composite, processing method, rubber belt and rubber roller applying composite, and manufacturing method
US20190359810A1